Influence of substrate wood species on the formation of antiviral properties of Inonotus rheades Pers. P. Karst. (1882) mycelium extracts regarding tick-borne encephalitis virus - M. A. Khasnatinov; T. G. Gornostai; I. S. Solovarov; M. S. Polyakova; G. A. Danchinova; G. B. Borovskii (Acta Biomedica Scientifica, 2022)
Background. The tick-borne encephalitis virus (TBEV) is one of the most dangerous and epidemiologically significant vector-borne pathogens. There is a need for effective antiviral agents for the treatment and prevention of this infection. Previously we found that the mycelium of Inonotus rheades grown on birch wood contains water-soluble substances with strong virulicidal properties against TBEV. It is necessary to check whether the mycelium of I. rheades can synthesize virulicidal substances from wood of other species.The aim: to study the antiviral properties of extracts of I. rheades mycelium grown on coniferous wood, both in the presence and in the absence of blue light during cultivation.Materials and methods. The mycelium of I.  rheades was grown on birch, pine, and fir wood. The direct virulicidal effect of the extract was evaluated by the decrease in the titer of the infectious virus incubated in the presence of the extract. The ability of the extract to inhibit the reproduction of the virus in infected cells was studied by  the  calculation of 50  % effective concentration (EC50). The toxicity of extracts for cells was evaluated based on the calculation of 50 % cytotoxic concentration.Results. Mycelium extracts grown on conifers under blue light do not cause a statistically significant decrease in the concentration of infectious TBEV (p = 0.2563). However, the BP10 extract (pine, blue light) inhibits TBEV reproduction in infected cells (EC50 = 0.28 ± 0.06 mg/mL). Toxicity for SPEV cell culture is low. In the extracts of conifers grown in the dark, no antiviral effect was found at all.Conclusions. The component composition and mechanism of the antiviral action of I. rheades extracts are determined by the species of the wood substrate. The most promising sources of new drugs in relation to TBEV appear to be extracts of I. rheades mycelium grown on birch and pine.